INOVASI PEMBELAJARAN IPS MELALUI METODE PEMBELAJARAN PERMAINAN TRADISIONAL - Rahman, Baitur (CV. Jendela Gagasan, 2024)
The development of the era has a big influence on social life in society. Not only does it touch adults, but it also changes the lifestyle of children who start rarely playing traditional games. Children tend to play modern games on smartphones or other sophisticated devices. In fact, the existence of traditional games can develop students' character. The writing in this article uses a qualitative descriptive method by analyzing sources from several documents, both from research results in the form of articles and books. The results in the discussion of this article found that traditional games are closely related to Social studies learning in schools. Traditional games can train students' social character which is useful in their social environment. This is in accordance with the aim of Social studies Sciences learning in schools, namely, to produce good citizens of the country. Learning social studies using a traditional game approach has great benefits, namely in which it can maintain traditional games as local wisdom and also trigger students' interest in social studies learning activities.